Library Service to Ethnic Minority Groups in USA - Patel, Jashu (Journal of Information and Knowledge, 1988)
The paper discusses briefly the implications for library service to the ethnic minority groups of U.S. population. It also attempts to (1) describe some developments and problems in library services to the ethnic minority groups in the U.S.A.; (2) describe some developments and suggest solutions to the problems of education and recruitment of students for ethnic librarianship; and (3) explore and learn any international lessons for mutual benefit. The role of the ethnic collections librarian and his/her contribution in the community is considered. A multi-cultural concept of librarianship is explored thus qualifying students or ethnic studies bibliographers to undertake research in ethnic librarianship in the original language. The major conclusions of the paper are drawn. The establishment of an international clearing house ethnic collection has been recommended.